Toward the development of a sporadic model of Alzheimer's disease: comparing pathologies between humanized APP and the familial J20 mouse models - Rentsch, Peggy; Ganesan, Kiruthika; Langdon, Alexander; Konen, Lyndsey M.; Vissel, Bryce (Frontiers in Aging Neuroscience, 2024)
Finding successful therapies for individuals with Alzheimer's disease (AD) remains an ongoing challenge. One contributing factor is that the mouse models commonly used in preclinical research primarily mimic the familial form of AD, whereas the vast majority of human cases are sporadic. Accordingly, for a sporadic mouse model of AD, incorporating the multifactorial aspects of the disease is of utmost importance.In the current study, we exposed humanized Aβ knock-in mice (hAβ-KI) to weekly low-dose lipopolysaccharide (LPS) injections until 24 weeks of age and compared the development of AD pathologies to the familial AD mouse model known as the J20 mice.At the early time point of 24 weeks, hAβ-KI mice and J20 mice exhibited spatial memory impairments in the Barnes maze. Strikingly, both hAβ-KI mice and J20 mice showed significant loss of dendritic spines when compared to WT controls, despite the absence of Aβ plaques in hAβ-KI mice at 24 weeks of age. Glial cell numbers remained unchanged in hAβ-KI mice compared to WT, and LPS exposure in hAβ-KI mice did not result in memory deficits and failed to exacerbate any other examined AD pathology.The study highlights the potential of hAβ-KI mice as a model for sporadic AD, demonstrating early cognitive deficits and synaptic alterations despite no evidence of Aβ plaque formation. These findings underscore the importance of considering multifactorial influences in sporadic AD pathogenesis and the need for innovative models to advance our understanding and treatment strategies for this complex disease.